Evaluation of Anatomical Variations on Paranasal Sinus CT - Yazıcı, Demet (ENT Updates, 2018)
Objective: The purpose of this study was to analyze and assess the frequency of anatomical variants of the paranasal sinuses as detected by multidetector computed tomography (MDCT) scanning. Methods: 225 patients (122 males, 103 females) in total, with a median age of 28 (range: 15-77) years were included in this retrospective study. Paranasal computed tomography was conducted in all cases. The scans were reviewed to discover the incidence of nasal septal deviation (NSD), variations of the nasal turbinates, ethmoidal air cells, paranasal sinus pneumatization, accessory pneumatization of the paranasal complex, variations in the sphenoid sinus-related structures and the optic nerve and Vidian canal classification type. Results: NSD was present in 124 (55.1%) of individuals, superior concha pneumatization in 30 (13.3%), middle concha pneumatization in 100 (44.4%), Agger nasi cells (ANC) in 192 (85.3%), Haller cells in 47 (20.9%), Onodi cells in 44 (19.6%), maxillary sinus hypoplasia in 6 (2.6%), frontal sinus hypoplasia in 29 (12.9%), frontal sinus aplasia in 7 (3.1%), sphenoid sinus hypoplasia in 7 (3.1%), uncinate process pneumatization in 12 (5.3%), anterior clinoid process (ACP) pneumatization in 60 (26.7%) and pterygoid process (PP) pneumatization in 75 (33.3%). Optic nerve Type 1 was found in 122 (54.2%) individuals, Type 2 in 29 (12.9%), Type 3 in 36 (16%) and Type 4 in 38 (16.9%). Vidian canal Type 1 was observed in 37 (16.4%), Type 2 in 95 (42.2%) and Type 3 in 93 (41.3%) individuals. Conclusion: The analysis of paranasal CT is crucial in the diagnosis of miscellaneous diseases of the paranasal sinuses. Anatomical variations in the sinuses are highly prevalent, so otorhinolaryngologists should be aware of these variations to allow them to reach precise diagnoses and avoid surgical complications.